Bisphosphonate guidelines for treatment and prevention of myeloma bone disease. Issue 8 (August 2017) - Lee, Oi Lin; Horvath, Noemi; Lee, Cindy; Joshua, Doug; Ho, Joy; Szer, Jeff; Quach, Hang; Spencer, Andrew; Harrison, Simon; Mollee, Peter; Roberts, Andrew W.; Talaulikar, Dipti; et al.
Abstract: Multiple myeloma (MM) is a haematological malignancy characterised by the clonal proliferation of plasma cells in the bone marrow. More than 80% of patients with MM display evidence of myeloma bone disease (MBD), characterised by the formation of osteolytic lesions throughout the axial and appendicular skeleton. MBD significantly increases the risk of skeletal‐related events such as pathologic fracture, spinal cord compression and hypercalcaemia. MBD is the result of MM plasma cells‐mediated activation of osteoclast activity and suppression of osteoblast activity. Bisphosphonates (BP), pyrophosphate analogues with high bone affinity, are the only pharmacological agents currently recommended for the treatment and prevention of MBD and remain the standard of care. Pamidronate and zoledronic acid are the most commonly used BP to treat MBD. Although generally safe, frequent high doses of BP are associated with adverse events such as renal toxicity and osteonecrosis of the jaw. As such, optimal duration and dosing of BP therapy is required in order to minimise BP‐associated adverse events. The following guidelines provide currently available evidence for the adoption of a tailored approach when using BP for the management of MBD.